Sub‐lethal effects of the neurotoxic pyrethroid insecticide Fastac® 50EC on the general motor and locomotor activities of the non‐targeted beneficial carabid beetle Platynus assimilis (Coleoptera: Carabidae). Issue 6 (4th October 2013) - Tooming, Ene; Merivee, Enno; Must, Anne; Sibul, Ivar; Williams, Ingrid
Abstract BACKGROUND Sub‐lethal effects of pesticides on behavioural endpoints are poorly studied in carabids (Coleoptera: Carabidae) though changes in behaviour caused by chemical stress may affect populations of these non‐targeted beneficial insects. General motor activity and locomotion are inherent in many behavioural patterns, and changes in these activities that result from xenobiotic influence mirror an integrated response of the insect to pesticides. Influence of pyrethroid insecticides over a wide range of sub‐lethal doses on the motor activities of carabids still remains unclear. RESULTS Video tracking of Platynus assimilis showed that brief exposure to alpha‐cypermethrin at sub‐lethal concentrations ranged from 0.01 to 100 mg L−1 caused initial short‐term (< 2 h) locomotor hyperactivity followed by a long‐term (>24 h) locomotor hypo‐activity. In addition, significant short‐ and long‐term concentration and time‐dependent changes occurred in general motor activity patterns and rates. CONCLUSION Conspicuous changes in motor activity of Platynus assimilis beetles treated at alpha‐cypermethrin concentrations up to 75 000‐fold lower than maximum field recommended concentration (MFRC) suggest that many, basic fitness‐related behaviours might be severely injured as well. These changes may negatively affect carabid populations in agro‐ecosystems. Long‐term hypo‐activity could directly contribute to decreased trap captures of carabids frequently observed after insecticide application in the field. © 2013 Society of Chemical Industry